LPSlow-Macrophages Alleviate the Outcome of Graft-Versus-Host Disease Without Aggravating Lymphoma Growth in Mice - Jeljeli, Mohamed; Chêne, Charlotte; Chouzenoux, Sandrine; Thomas, Marine; Segain, Benjamin; Doridot, Ludivine; Nicco, Carole; Batteux, Frédéric (Frontiers in Immunology, 2021)
Despite significant therapeutic advances, Graft-versus-Host-Disease (GvHD) remains the main life-threatening complication following allogeneic hematopoietic stem cell transplantation. The pathogenesis of GvHD is dominated by a dysregulated allogeneic immune response that drives fibrosis and autoimmunity in the chronic forms. A Multitude of cell therapy approaches, including infusion of myeloid cells, has been proposed to prevent GvHD through tolerance induction but yielded variable results. Myeloid cells like macrophages can be reprogrammed to develop adaptive-like features following antigenic challenge to reinforce or inhibit a subsequent immune response; a phenomenon termed ‘trained immunity’. Here we report that, whereas LPSlow-trained macrophages elicit a suppressor effect on allogeneic T cell proliferation and function in vitro in an IL-10-dependent manner, BCG-trained macrophages exert an opposite effect. In a murine model of sclerodermatous chronic GvHD, LPSlow-trained macrophages attenuate clinical signs of GvHD with significant effects on T cell phenotype and function, autoantibodies production and tissue fibrosis. Furthermore, infusion of LPSlow-macrophages significantly improves survival in mice with acute GvHD. Importantly, we also provide evidence that LPSlow-macrophages do not accelerate A20-lymphoma tumor growth, which is significantly reduced upon transfer of BCG-macrophages. Collectively, these data indicate that macrophages can be trained to significantly inhibit in vitro and in vivo alloreactive T cell proliferation without exhibiting pro-tumoral effect, thereby opening the way to promising clinical applications.